Cotyledon persistence in the seedling as a parameter for evaluation of aluminum tolerance in leucaena leucocephala - Maluf, Angela Maria; Martins, Paulo Sodero; Maluf, Wilson Roberto (Pesquisa Agropecuaria Brasileira, 2014)
Cotyledon persistence in seedlings grown under aluminum stress, previously found to be a good parameter to discriminate large differences In Al tolerance among Leucaena leucocephala (Lam.) de Wit. introductions, was evaluated as a method to discriminate different levels of tolerance between and within tolerant populations. Twelve single plant progenies obtained from three tolerant populations, one intolerant introduction and one single-plant introduction of unknown tolerance were screened in nutrient solution under 9 ppm of Al. Percentage of plants with yellowed or fallen cotyledons and total dry weight of the seedlings were recorded. The former parameter was efficient not only in the discrimination of tolerant versus intolerant populations, but also in the discrimination of different levels of tolerance within tolerant populations, contrasting in this respect with the latter parameter.